Analisis Kualitatif Implementasi Hadirr.com dalam Mengatasi Fraud Absensi pada Perusahaan Ritel Multilokasi : Studi Fenomenologi di 72 Cabang Banten-Bogor - David Christian; Safuan Safuan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
A manual attendance system was previously used to manage the attendance list of each employee. However, this application causes attendance fraud. Therefore, the attendance system was changed into a digital form to reduce attendance fraud and improve discipline. This qualitative study was conducted through the phenomenological method by examining the implementation of the Hadirr.com digital attendance system in a 72-branch retail network in Banten-Bogor. Data in this study was collected through in-depth interviews with 45 informants (HRD managers, branch supervisors, and employees) and participatory observation for 6 months. The findings revealed three main themes, namely the absenteeism fraud patterns that developed before and after implementation, changes in work culture related to attendance and discipline post-implementation, and social interaction patterns formed due to implementation. This study provides a conceptual framework on the determinants of a successful digital time attendance system in a multi-site retail environment.